Damage tolerance of metallic aircraft structures : materials and numerical modelling /: materials and numerical modelling. (2018) - Tavares, Sérgio M. O; Castro, Paulo M. S. Tavares de (Paulo Manuel Salgado Tavares), 1950-
No abstract available